P03 Clinician variation in treating childhood wheeze in Emergency Departments of the United Kingdom AND Ireland – an international survey. (7th April 2014) - Lyttle, MD; O'Sullivan, R; Doull, I; Morris, I; Powell, CVE
Abstract : Aims: National clinical guidelines for childhood wheeze have existed for several years. Despite being one of the commonest reasons for childhood Emergency Department (ED) attendance, significant variation in practice has been demonstrated in other settings. The aim of this evaluation was to examine variations in practice of clinicians working in EDs in the UK and Ireland. Methods: In March 2013, PERUKI EDs (generic and paediatric) were invited to respond to a departmental survey. Consultant clinicians responsible for childhood wheeze management within those EDs were also invited to participate outlining their personal practice. Information regarding pharmacological and other management strategies was sought, including approaches to inhaled and intravenous (IV) therapies. Results: 30 (100%) EDs and 186 (80%) clinicians responded. 29 (97%) EDs had wheeze guidelines and 13 (43%) had care pathways. Amongst clinicians variation existed in dose, timing and frequency of inhaled bronchodilators for all levels of severity. On escalation to IV bronchodilators in severe wheeze 100 (54%) preferred salbutamol as their first line agent, 54 (29%) Magnesium Sulphate (MgSO4 ) and 27 (15%) aminophylline. 88 (47%) routinely administered IV bronchodilators sequentially and 30 (16%) concurrently, with the remainder basing either approach on case severity. 146 (79%) continued inhaled therapy after commencing IV bronchodilators. Of 173 who used IV salbutamol, 149 (86%) gave rapid boluses, 21 (12%) a longer loading dose, and 167 (97%) an ongoing infusion, each with a range of doses and durations. Of 176 who used IV MgSO4, all used a bolus only. 44 (24%) used non-invasive ventilation. Conclusions: Significant variation in ED management of childhood wheeze as reported by consultant clinicians exists despite the presence of national guidance. This reflects the lack of evidence in key areas of childhood wheeze and emphasises the need for further robust multi-centre research studies.